Endovascular Treatment of Cerebral Artery Aneurysms during Pregnancy: Report of Three Cases - Meyers, Philip M.; Halbach, Van V.; Malek, Adel M.; Phatouros, Constantine C.; Dowd, Christopher F.; Lawton, Michael T.; Lempert, Todd E.; Higashida, Randall T. (American Journal of Neuroradiology, 2000)
Summary: Historically, surgical management of cerebral aneurysms during pregnancy has been controversial. Debate originally focused on early versus late intervention, before or after delivery of the fetus. More recently, treatment has centered on rapid intervention. We describe the endovascular treatment of cerebral artery aneurysms with Guglielmi detachable coils in three pregnant women.